Clinical analysis of the care pathway among women who underwent mastectomy following breast cancer in Cameroon - Alvy Gislaine Magne Fongang; Martial Nguegno Fouadjo (Journal of Psychological Perspective, 2026)
This article examines the care trajectory and psychological experience of women who have undergone mastectomy following breast cancer in Cameroon, using a qualitative clinical and interpretative approach. Based on semi-structured clinical interviews with three women receiving follow-up care in an oncology department in the Western region of Cameroon, the study highlights how the care pathway extends beyond biomedical treatment and is shaped by sociocultural meanings, economic constraints, family dynamics, and spiritual interpretations. Findings reveal diagnostic delays, therapeutic wandering, and the frequent coexistence of biomedical medicine, traditional practices, and religious healing in patients’ trajectories. Mastectomy emerges as a major embodied disruption affecting body image, self-esteem, sexuality, marital relationships, and feminine identity, often intensified by stigma and fear of social judgment. However, the study also identifies resilience processes supported by children, family bonds, faith, and opportunities for psychological verbalization. This research contributes to the literature by emphasizing mastectomy as a relational and meaning-making experience embedded in a plural medical and cultural context. Practical implications include the need for earlier diagnostic communication, improved health education, partner-sensitive counseling, and integrated psychosocial support throughout the care pathway.